Sustainable supply chains: Marks & Spencer’s Plan A - Bernon, Mike (Henry Stewart Talks, 2018)
This case study examines Marks & Spencer’s ‘Plan A’ brand strategy for sustainability in general and, in particular, the development of Marks & Spencer’s new ‘Plan A’ vehicle. The new lorry has not only reduced the company’s carbon emissions but has also lowered costs by increasing load capacity while reducing fuel consumption.